The MID1 protein is a central player during development and in disease - Winter, Jennifer; Basilicata, M. Felicia; Stemmler, Marc; Krauss, Sybille (Frontiers in Bioscience, 2016)
Loss-of-function mutations in the MID1 gene cause a rare monogenic disorder, Opitz BBB/G syndrome (OS), which is characterized by malformations of the ventral midline. The MID1 gene encodes the MID1 protein, which assembles a large microtubule-associated protein complex. Intensive research over the past several years has shed light on the function of the MID1 protein as a ubiquitin ligase and regulator of mTOR signalling and translational activator. As a central player in the cell MID1 has been implicated in the pathogenesis of various other disorders in addition to OS including cancer and neurodegenerative diseases. Influencing the activity of the MID1 protein complex is a promising new strategy for the treatment of these diseases. In this review we will summarize the current knowledge about MID1, its involvement in the pathogenesis of OS and other diseases and possible strategies for therapy development.
EVALuna2:10214